Pertimbangan Hakim dalam Menjatuhkan Pidana terhadap Tindak Pidana Pencurian dengan Pemberatan yang Dilakukan oleh Anak - Ida Bagus Agung Pariama Manuaba; I Nyoman Sujana; Ni Made Sukaryati Karma (Warmadewa Press, 2020)
Judge's considerations are matters which are the basis or are considered by the judge in deciding a crime case. Crime Theft is an act that is classified as a general crime in which a crime against the property of another person. Theft with weighting is a criminal act of theft which in its implementation is accompanied by certain elements so that it is more severe and threatened with higher penalties. Child is a person who is not yet eighteen (18) years old, including those who are still in the womb. In settling a child case, the judge must consider the report in the trial regarding the child concerned. This study aims to determine the criminal considerations and sanctions imposed by the judge on criminal theft with weighting carried out by children. This study uses a normative legal research method with a statutory approach, conceptual approach and case approach. The legal materials studied are primary legal materials, secondary legal materials and tertiary legal materials. The results of this study indicate the judge's judgment in imposing a crime against a child who commits a crime of theft by weighting it based on the elements of the crime committed as well as things that alleviate and incriminate the crime against the child. Criminal sanctions imposed by a judge against a child who commits an act of theft by weighting based on the Court's Decision and the provisions of Article 363 paragraph (1) of the 4th KtoP Jungto Article 65 paragraph (1) of the Criminal Code and other laws relating to the case state that the child is proven legally and convincingly guilty as well as convicting a child of seven months in prison.